Characterization of Cantera Stone From Hidalgo State, México. Viability Study for Recycling and Reusing of Wastes. - E. Salinas R. (The Minerals, Metals and Materials Society, 2009)
This work is related with a whole characterization of cantera stone, to establish its characteristics that can give it an additional value for the reuse and reutilization of dust, slurries and small pieces of stone which can be treated as wastes. The obtained results reflects that the residues studied can be used as substitutes of feldspars in the production of pieces of ceramic, and also in the elaboration of paints for the same pieces according to the mixes that can be made with the variation of Na2O, CaO and K2O. According to the humidity proofs and specific gravity done, this material can be proposed as a soil improver into hydroponics systems, leading so an important alternative for food production in zones leaking of water. In the same way, it was found the possibility of use this material as a seal 3A in processes of asphalting of roads, highways and streets.